Relationship between social economic status and family's clean and healthy behavior (PHBS) in Tesa Village, Laenmanen District, 2020 - Brigita Dina Manek; Matilda Bupu Rian; Atalia Bilimangngi (Alma Ata University Press, 2021)
Background: Economy is the main factor related to the implementation of PHBS in Tesa village, Malaka Regency. Objectives : This study aims to determine the relationship between Social economic Status and Clean and Healthy Family Behavior (PHBS) in Tesa Village, Malaka Regency in 2020. Methods: The research design is a correlational analytic study. The design of the study is correlational analytic study. The population is all family in Tesa village N = 124 respondents with a simple random sampling technique obtained 94 samples of respondents. The instrument used was a questionnaire sheet about social economic status and PHBS.The instrument used was a questionnaire sheet about social economic status and PHBS. The results were analyzed by using the proportional cluster. Results: The results of the research show that almost all (76.6%) had good Clean and Healthy Behavior (PHBS) and nearly half 47 (50.0%) had the Prosperous Social-Economic II status. The results from cross tabulation shows the relationship between Social Economic status and PHBS which is found that there were 33 respondents (34.0%) with moderate PHBS. The result of statistical test using Spearman rank test shows p=0.000 is smaller than the value of α=0.05 (0.000< 0.05) so that H0 is rejected and H1 is accepted. This means that there is a relationship between the social economic status of the family and PHBS in 2020. Conclusions: It can be concluded that the higher the social economic status of the family between education, work and overall economic conditions, the better the behavior of a clean and healthy life is expected and the family will protect it more by seeking health-related information